Cost-effectiveness analysis of eliminating industrial and all trans fats in England and Wales: modelling study. (9th September 2016) - Pearson-Stuttard, Jonathan; Hooton, William; Critchley, Julia; Capewell, Simon; Collins, Marissa; Mason, Helen; Guzman-Castillo, Maria; O'Flaherty, Martin
Abstract: Introduction: Coronary heart disease (CHD) remains a leading cause of UK mortality. Dietary trans fats (TFA) represent a powerful CHD risk factor. However, UK efforts to reduce intake have been less successful than other nations. We modelled the potential health and economic effects of eliminating industrial and all TFA up to 2020. Methods: We extended the previously validated IMPACTsec model, to estimate the potential effects on health and economic outcomes of mandatory reformulation or a complete ban on dietary TFA in England and Wales from 2011 to 2020. We modelled two policy scenarios: 1) Elimination of industrial TFA consumption, from 0.8% to 0.4% daily energy 2) Elimination of all TFA consumption, from 0.8% to 0% Results: Elimination of industrial TFA across the England and Wales population could result in approximately 1600 fewer deaths per year, with some 4000 fewer hospital admissions; gaining approximately 14 000 additional life years. Health inequalities would be substantially reduced in both scenarios. Elimination of industrial TFA would be cost saving. This would include approximately £100 m saved in direct healthcare costs. Elimination of all TFA would double the health and economic gains. Conclusions: Eliminating industrial or all UK dietary intake of TFA could substantially reduce CHD mortality and inequalities, while resulting in substantial annual savings.